1978
DOI: 10.1159/000122766
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic and Dopaminergic Regulation of GH and Prolactin in Baboons

Abstract: Aminergic regulation of growth hormone (GH) and prolactin (Prl) was studied in male adolescent baboons by i.v. infusion of dopamine (DA), norepinephrine (NE), thyrotropin-releasing hormone (TRH), phentolamine, haloperidol, and inhibitors of DA-β-hydroxylase and peripheral decarboxylase. 20-min infusion of DA (40 µg/kg·min) and 60-min infusion of NE (0.4 µg/kg·min) stimulated GH release. The DA-induced GH release was suppressed by concomitant infusion of FLA 63 (inhibitor of NE synthesis from DA) and by phentol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…These observations extend earlier findings in monkeys with other dopamine-|l-hydroxylase inhibitors [10]. Sponta neous GH secretion was markedly suppressed by DDTC; both the frequency and amplitude of the GH peaks were significantly diminished when compared to baseline levels.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These observations extend earlier findings in monkeys with other dopamine-|l-hydroxylase inhibitors [10]. Sponta neous GH secretion was markedly suppressed by DDTC; both the frequency and amplitude of the GH peaks were significantly diminished when compared to baseline levels.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates that DDTC not only abolishes GH release by blocking NE synthesis but also that its action may, in part, be mediated by an increase of endogenous SS release. The intrahypothalamic dopamine increase may account for the SS release; in other settings dopamine has been shown to stimulate SS release [19][20][21], and dopamine administration into the medial basal hypothalamus has been shown to re duce GH release in young baboons [10], GHRH acts directly at the pituitary level, but its effects can be inhibited noncompetitively by SS, even when GHRH is given at a maximally stimulating dose [18]. The diminution of GH responses to GHRH after DDTC thus points to a possible effect of DDTC to increase endogenous SS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, whole tissue content studies completed in both rats and guinea pigs have demonstrated that NE turnover in the arcuate significantly increases on the afternoon of proestrus [23, 24]. In addition, microinjection of NE into the medial basal hypothalamus of male baboons has been shown to initiate a significant elevation in serum levels of PRL [25]. Together, these studies suggest that the α 2 -receptor may have a role in modulating dopamine activity within the arcuate, and subsequently, circulating levels of PRL.…”
Section: Introductionmentioning
confidence: 99%
“…* This work was presented in part at the Endocrine Society Annual Meeting, Atlanta, 1990. Norepinephrine (NE) is an important regulator of GH secretion in the brain (9,10). Exogenous administration of NE or other a-adrenergic agonists evokes GH secretion (11,12). Blockade of NE synthesis using the dopamine-/?-hydroxylase (DBH) inhibitor diethyldithiocarbamate (DDTC) (13,14) has been studied widely as a means of acutely suppressing GH secretion.…”
mentioning
confidence: 99%